Adrenal steroids modulate the immune response during Brucella abortus infection by a mechanism that depends on the regulation of cytokine production - Gentilini, Maria Virginia (2015)
Human brucellosis is a protean disease with a diversity of clinical signs and symptoms resulting from infection with Brucella species. Recent reports suggest a cross-regulation between adrenal steroids (cortisol and dehydroepiandrosterone [DHEA]) and the immune system. Monocytes and macrophages are the main replication niche for Brucella. Therefore, we investigated the role of adrenal hormones on the modulation of the immune response mediated by macrophages in B. abortus infection. Cortisol treatment during B. abortus infection significantly inhibits cytokine, chemokine, and MMP-9 secretion. In contrast, DHEA treatment had no effect. However, DHEA treatment increases the expression of costimulatory molecules (CD40, CD86), the adhesion molecule CD54, and major histocompatibility complex class I (MHC-I) and MHC-II expression on the surface of B. abortus-infected monocytes. It is known that B. abortus infection inhibits MHC-I and MHC-II expression induced by gamma interferon (IFN-γ) treatment. DHEA reverses B. abortus downmodulation of the MHC-I and -II expression induced by IFN-γ. Taken together, our data indicate that DHEA immune intervention may positively affect monocyte activity during B. abortus infection.